2010
DOI: 10.1063/1.3462317
|View full text |Cite
|
Sign up to set email alerts
|

Very thin transparent, conductive carbon nanotube films on flexible substrates

Abstract: We investigate the morphological, electrical, and optical properties of carbon nanotube thin films, focusing on films with transmittance, T Ͼ 90%. For films with T Ϸ 90% we measure sheet resistance of R s Ͻ 400 ⍀ / ᮀ. However, we show that optoelectrical properties, such as dc and dc / Op , degrade with decreasing film thickness, t, for percolating nanotube networks, i.e., those with t Ͻ 20 nm and T Ͼ 90%. Thus, while reducing t can give T Ͼ 99%, the corresponding R s increases to Ͼ40 k⍀ / ᮀ. Acid treatment im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
111
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(118 citation statements)
references
References 17 publications
(17 reference statements)
3
111
0
1
Order By: Relevance
“…17 Carbon nanotubes, silver nanowires and graphene sheets exhibit considerable conductivity, but limited stretchability and transmittance. 14,[18][19][20] Whereas making highly stretchable and transparent electronic conductors has been challenging, a recent work has reported dielectric elastomer transducers using hydrogels as stretchable, transparent, ionic conductors. 21 These transducers can operate at frequencies beyond 10 kilohertz and voltages above 10 kilovolts.…”
Section: Introductionmentioning
confidence: 99%
“…17 Carbon nanotubes, silver nanowires and graphene sheets exhibit considerable conductivity, but limited stretchability and transmittance. 14,[18][19][20] Whereas making highly stretchable and transparent electronic conductors has been challenging, a recent work has reported dielectric elastomer transducers using hydrogels as stretchable, transparent, ionic conductors. 21 These transducers can operate at frequencies beyond 10 kilohertz and voltages above 10 kilovolts.…”
Section: Introductionmentioning
confidence: 99%
“…Dispersing individual CNTs in a solution is quite difficult, and CNTs tend to form bundles with sizes of 10-25 nm even if a surfactant is used. [19][20][21] These sizes correspond to l of more than 10.…”
Section: Gate Electrostaticsmentioning
confidence: 99%
“…They found that the data tend to deviate severely from the fits for thinner films, as seen from Figure 2. This deviation has been observed before [10][11][12] and tends to occur for films with T between 50% and 92%.Thus,σ dc /σ ac fails to describe the relationship between T and Rsin the relevant regime. The deviation from bulk-like behavior as described in Equation1, can be explained by percolation effects [13].…”
Section: Optoelectronic Propertiesmentioning
confidence: 87%